2013
DOI: 10.1242/jcs.128512
|View full text |Cite
|
Sign up to set email alerts
|

The telomere-associated homeobox-containing protein TAH1 participates in telomere maintenance in ALT Cells

Abstract: SummaryThe majority of cancer cells rely on elevated telomerase expression and activity for rapid growth and proliferation. Telomerase-negative cancer cells, by contrast, often employ the alternative lengthening of telomeres (ALT) pathway to maintain telomeres. ALT cells are characterized by long and dynamic telomeres and the presence of ALT-associated promyelocytic leukemia (PML) bodies (APBs). Previous work has shown the importance of APBs to the ALT pathway, but their formation and precise role remain uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 45 publications
(51 reference statements)
1
22
0
Order By: Relevance
“…Recently, HMBOX1 was found to bind double-stranded telomere repeats and associate with the active telomerase complex to support telomerase-dependent telomere elongation 3 . Moreover, HMBOX1 participated in telomere maintenance in alternative lengthening of telomere (ALT) cells, which extended their telomeres independent of telomerase 4 .…”
mentioning
confidence: 99%
“…Recently, HMBOX1 was found to bind double-stranded telomere repeats and associate with the active telomerase complex to support telomerase-dependent telomere elongation 3 . Moreover, HMBOX1 participated in telomere maintenance in alternative lengthening of telomere (ALT) cells, which extended their telomeres independent of telomerase 4 .…”
mentioning
confidence: 99%
“…Next, we investigated whether CIRP could bind directly to TERC in vitro . For this purpose, bacterially purified CIRP-GST proteins (Figure 4B ) were used in the EMSA ( 76 ). The TERC RNA probe was in vitro transcribed and radio-labeled before being incubated with the recombinant proteins.…”
Section: Resultsmentioning
confidence: 99%
“…In the study using MEFs, 471 proteins were found to associate with telomeres regardless of telomere status ( 42 ). The technique QTIP utilizes SILAC coupled with mass spectrometric analysis to compare and identify quantitative differences between telomere proteins ( 34 ). A total of 258 telomere-associated proteins were identified by QTIPin HeLa cells ( 43 ).…”
Section: Construction and Contentmentioning
confidence: 99%
“…In addition, some proteins with DNA binding activities (not specific for telomere DNA sequence) can directly bind to telomere DNA. For instance, we have shown that TAH1/HMBOX1/HOT1 directly binds to telomeric double-stranded DNA and become a part of the interaction network ( 34 , 35 ).…”
Section: Introductionmentioning
confidence: 99%